Two-Dimensional Droplet Digital PCR as a Tool for Titration and Integrity Evaluation of Recombinant Adeno-Associated Viral Vectors - Furuta-Hanawa, Birei (Hum Gene Ther Methods, 2019)
Recombinant adeno-associated virus (rAAV) vectors have recently been widely utilized for in in vivo gene therapy. The clinical dose definition of AAV vector requires the exact quantification as starting doses and for dose-escalation studies. Vector genome (vg) copies measured by quantitative PCR (qPCR) are commonly used for rAAV vector titration, and rAAV vector plasmids DNA is often used for qPCR standards, although the rAAV reference standard materials (RSMs) for serotypes 2 and 8 (rAAV2RSM and rAAV8RSM) are available from American Type Culture Collection. However, qPCR-based determination of the AAV vg is affected by the selection of the qPCR standard and the amplification target sites. In this study, we have developed a new PCR method, two-dimensional droplet digital PCR (2D ddPCR), for the absolute quantitation of target DNA and for evaluating the stability of the rAAV vector. The number of vg copies of rAAV2RSM determined by qPCR dramatically changed when standard plasmid DNAs with different conformations were treated with restriction enzymes, suggesting that qPCR amplification is significantly affected by the secondary structure of the standard. In contrast, the number of vg copies determined by ddPCR was unaffected by using primer probes for different positions of target sites or by the secondary structure conformation of the vg. Furthermore, the integrity of the AAV vg can be monitored using 2D ddPCR with fluorescein- and hexachloro-6-carboxy-fluorescine–labeled probes targeting different positions in the same rAAV genome. The titer of intact rAAV was highly correlated with rAAV activity in an accelerated (37°C) stability study. 2D ddPCR is a useful tool for rAAV vector quantitation and quality evaluation.